Pengukuran Kesilindrisan Hasil Proses Pemotongan Mesin Bubut Untuk Mengetahui Kemampuan Mesin Menghasilkan Suatu Produk - Ariyanto Ariyanto; Husman Husman (Manutech : Jurnal Teknologi Manufaktur, 2018)
The ability of machine tools to produce a product of good quality is needed by the industrial industry that exists today. Industrial industries that use machine tools are not only industries that produce products in the form of a tool or machine, machine tools are also widely used by industries or institutions that serve machine repair and providers of skills training. The quality of the machine measured using the geometry of the workpiece resulting from the machining process can be in the form of roundness, cylindrecity, tapers and other geometric shapes. The use of machine tools that continue for several years can result in a decrease in the ability of the machine to produce a product. The use of a long horizontal doall lt13 lathe will produce a form of workpiece cylindricity that is not the same as the condition of the the new machine tools, therefore testing activities are carried out by cutting the machine and seeing what the cylindrical value of the specimen is capable of achieving . From the results of the testing that has been carried out on a horizontal lathe as many as eight units, the values of cylindrical difference are different for each machine. The highest value of cylindricity is produced by lathes with machine number 8 and the smallest cylindrical value produced by lathes with machine number 3. The greatest tolerance is achieved in the quality of IT (international tolerance) 11 tolerance and the lowest is achieved in IT tolerance quality 10.